20 - 30-year-old employee the relationship between the forgiveness motives and the perceived stress indicators - Dudkina, Aija; Jodis, Henrijs (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2015)
The purpose of this study is to explore the theory and real-life manifestation of the forgiveness motives among employees with high and low stress levels. The target group of 20- to 30-year olds has been selected for the study because this life-period is considered particularly important in a human's life. It is a time of self-actualisation, starting a family, seeking stability and emotional balance. Few attempts to analyse the psychology of forgiveness in the working environment have so far been attempted in Latvia. The study aims to establish whether there exists a statistically significant correlation between the forgiveness motives and the perceived level of stress. Study builds on "An Empirical Test of Forgiveness Motives „Effects on Employees” Health and Well - Being" (Cox, Bennett, Tripp, Aquino, 2012) which revealed five types of motives for forgiveness: apology, moral, religious, relationship, and lack of alternatives. The studywaslinguisticallyadapted questionnaire (Trainer Forgiveness scale (1991), modified by Susie S. Cox, Rebecca J. Bennett, Thomas M. Tripp, & Karl Aquino, 2012)"Forgiveness Motives"who to determine the forgiveness motives among the target group. To establish the stress levels, a shortened version of the perceived stress questionnaire was used. The findings of the study support those of the research (Cox et al., 2012). There does exist a statistically significant correlation between the moral scale and the perceived stress. People who forgive primarily for moral reasons experience less stress. Equally, people who forgive primarily due to lack of alternatives experience higher levels of stress.